Regional influences on reconstructed global mean sea level. Issue 7 (14th April 2017) - Natarov, Svetlana I.; Merrifield, Mark A.; Becker, Janet M.; Thompson, Phillip R.
Abstract: Reconstructions of global mean sea level (GMSL) based on tide gauge measurements tend to exhibit common multidecadal rate fluctuations over the twentieth century. GMSL rate changes may result from physical drivers, such as changes in radiative forcing or land water storage. Alternatively, these fluctuations may represent artifacts due to sampling limitations inherent in the historical tide gauge network. In particular, a high percentage of tide gauges used in reconstructions, especially prior to the 1950s, are from Europe and North America in the North Atlantic region. Here a GMSL reconstruction based on the reduced space optimal interpolation algorithm is deconstructed, with the contributions of individual tide gauge stations quantified and assessed regionally. It is demonstrated that the North Atlantic region has a disproportionate influence on reconstructed GMSL rate fluctuations prior to the 1950s, notably accounting for a rate minimum in the 1920s and contributing to a rate maximum in the 1950s. North Atlantic coastal sea level fluctuations related to wind‐driven ocean volume redistribution likely contribute to these estimated GMSL rate inflections. The findings support previous claims that multidecadal rate changes in GMSL reconstructions are likely related to the geographic distribution of tide gauge stations within a sparse global network. Key Points: We quantify the contribution of different oceanic regions to the reduced space optimal interpolation derived historical GMSL reconstruction We find that the North Atlantic plays a singular role in determining the shape of the reconstructed GMSL prior to the 1950s Limited tide gauge network resolution leads to conflation of changes in regional sea level with global sea level prior to 1950s